PENGARUH TAX PLANNING, UKURAN PERUSAHAAN DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN - TIO FANNY ANGELE; SOVIA LOLITA A. PARDEDE; CORINNA WONGSOSUDONO (JURNAL ILMIAH KOHESI, 2022)
The firm value is an important thing for companies and investors where the firm value is an indicator in seeing the level ofsuccess obtained by the company, this is refers to the high and low prices of existing shares. If the stock price in company ishigher that’s also can be impacted on the firm value’s companies. The purpose of this study is to determine the effect of taxplanning, firm size and profitability on firm value in food and beverages industry companies listed on the Indonesia StockExchange (IDX) from 2015-2019. Sampling in this study was carried out by purposive sampling method and the analysis wastested by using quantitative analysis methods. From this study, it was found that tax planning and firms size partially had noeffect on firm value, while profitability partially affected firm value. For the simultaneous results obtained that tax planning,firm size and profitability simultaneously affect the firm value.